Survey on EFL Students’ Writing Anxiety: Level, Types, and Causes - Syarifudin Syarifudin (Makassar State University, 2020)
This study attempts to investigate the EFL learners’ writing anxiety. Being more specific, the researcher was interested to measure the EFL learners’ writing anxiety levels, to find out types of writing anxieties (i.e., Somatic Anxiety, Cognitive Anxiety, Avoidance Behavior), and elaborate the triggering factors of writing anxiety. The research subjects were 28students who registered for Essay Writing in English Study Program; Two different questionnaires were administered to gather the data; SLWAI questionnaire designed by Cheng (2004) and another questionnaire developed by Zhang (2011). To investigate the level of writing anxiety and its types, the data from the SLWAI questionnaire were analyzed and calculated to find the mean. Moreover, to find out the causes of writing anxiety, the data from the second questionnaire were ranked from 1-7 based on the most chosen items. The findings showed that students experience high level of anxiety (M=65.86, >65). Then the most common type of anxiety was Cognitive Anxiety, and the mean score is 23.9 in which it was the highest of all the types. Furthermore, linguistics difficulties (82%), lack of topical knowledge (68%), and insufficient writing technique (60%) were the dominant sources of students’ writing anxiety